Two new species of Quintinia (Paracryphiaceae) with notes on the species from New Caledonia and Vanuatu - Pillon, Yohan; Hequet, Vanessa (Phytotaxa, 2019)
The taxonomy of Quintinia (Paracryphiaceae) in New Caledonia and Vanuatu is reviewed. All names validly published in Quintinia in the two archipelagos are discussed and lectotypified where necessary. Two new species are described: Q. hyehenensis and Q. sessiliflora. Six species are thus recognized in New Caledonia: Q. hyehenensis, Q. major, Q. minor, Q. oreophila, Q. sessiliflora, and Q. media; the latter also extends to Vanuatu. Sexual systems are discussed and it seems that contrary to previous reports, Quintinia is almost entirely dioecious on these islands. The moderately high manganese concentration in the leaves of Q. sessiliflora is discussed.